Facile preparation of amidoxime-functionalized Fe3O4@SiO2-g-PAMAM-AO magnetic composites for enhanced adsorption of Pb(ii) and Ni(ii) from aqueous solution - Yimin, Dai; Danyang, Liu; Jiaqi, Zou; Shengyun, Wang; Yi, Zhou (RSC advances, 2019)
In this paper, using amidoxime as a functional monomer, different generations of polyamidoxime dendrimer magnetic microspheres (Fe3O4@SiO2-g-PAMAM-AO) were fabricated to adsorb Pb2+ and Ni2+ in aqueous solution. The magnetic adsorbents were characterized by FTIR, XRD, SEM, XPS, TEM, EDS, TGA and BET. The effects of different factors (such as solution pH, adsorption time, adsorption temperature, adsorbent dosage etc.) on adsorption were evaluated. Fe3O4@SiO2-g-PAMAM-AO has a maximum Pb(ii) adsorption of 157.25 mg g−1 (100 mg L−1) at pH 5.5. Furthermore, Fe3O4@SiO2-g-PAMAM-AO showed an excellent adsorption performance for the removal of Ni(ii) with a maximum adsorption capacity of 191.78 mg g−1 (100 mg L−1) at pH 8.0. The sorption isotherm data fitted the Freundlich isotherm model well. Adsorption kinetics analysis showed that it was best described by the pseudo-second-order rate model. Desorption experiment results showed that the adsorbent can be reused in the adsorption–desorption cycles.